Influence of injectable progesterone on the pregnancy rate of heifers receiving bovine embryos - da Silva, Caio Cezar; Gregianini, Helton Aparecido Garcia; Gregianini, Jennifer Teodoro Ferreira; Dell'Aqua, José Antônio [UNESP]; Diniz, Jefferson Viana Alves; Maia, Gerbson Francisco Nogueira; Peixoto, Renato Mesquita; Satrapa, Rafael Augusto (Universidade Federal do Rio Grande do Sul, 2021)
Background: In vitro embryo production (IVEP) allows the spread of superior animal genetics, but pregnancy rates show a high variability with this biotechnique. In the initial stage of pregnancy, progesterone plays a fundamental role in uterine preparation, acting on embryonic growth, implantation, and development. However, on the day of the IVEP transfer to the recipients, progesterone levels may be lower than that expected, influencing the uterine environment and, consequently, the pregnancy rate. Therefore, the objective of this study was to evaluate the pregnancy rate in heifers after the administration of injectable progesterone (P4) in the fixed-time embryo transfer (FTET) protocol. Materials, Methods & Results: The experiment was conducted inside a rural property near the city of Rio Branco, Acre, Brazil. The experimental group consisted of 232 animals, including 78 zebuine (Bos indicus) and 154 mixed (½ blood B. indicus and ½ blood B. taurus) animals, aged between 16 and 24 months, with a mean weight of 300 and 330 kg for zebuine and mixed animals, respectively. The selected animals were previously synchronized using the progesterone-estrogen-prostaglandin-estrogen protocol. Embryo transfer was performed on day 18 of the protocol, which was 9 days after the removal of intravaginal progesterone implant. On day 15 of the protocol, that is, 144 h (6 days) after the device removal, the animals were randomly distributed into two experimental groups: Control Group (CG; 0.5 mL of 0.9% saline solution, intramuscular) and Treated Group (P4G; 0.5 mL of injectable P4, 150 mg, intramuscular). Chi-square test was used for the statistical analysis of the pregnancy rate at a 5% probability. After 23 days of embryo transfer, pregnancy was diagnosed by ultrasonography. The general pregnancy rate, considering all groups (CG and P4G) and breeds included, was 55.17% (128/232). The pregnancy rates of the P4G and CG groups, regardless of breeds, were 55.08% (65/118) and 55.26% (63/114), respectively, with no statistical difference (P = 0.8344). Angus animals presented a similar pregnancy rate in the P4G and CG groups of 54.93% (39/71) and 57.83% (48/83), respectively. Furthermore, similar results were found for the Nellore breed, with no difference in pregnancy rate between the CG (55.81%, 24/43) and P4G (48.57%, 17/35) groups. Discussion: The strategy of using P4 to increase the pregnancy rate is very widespread in fixed-time artificial insemination (FTAI) protocols, although differences still exist. The literature presents zero or negative effects, as in this study, when exogenous P4 was used to increase endogenous P4 concentrations and, consequently, the pregnancy rate. However, some studies demonstrated the beneficial effects of increasing blood P4 concentrations, and that the increased fertility depends on the method and time of P4 supplementation and the animal's physiological state. In this context, the fact that the injectable progesterone supplementation did not increase the pregnancy rate in this study is justified mainly by factors such as the animal category used (heifers), time of P4 supplementation (day 4 after ovulation), biotechnology used (FTET), and the heterogeneous characteristics related to phases of the estrous cycle of heifers. Supplementation with 150 mg of injectable long-acting progesterone intramuscularly did not interfere in the pregnancy rate of Angus and Nellore heifers receiving bovine embryos.
Influência da progesterona injetável na taxa de prenhez de novilhas receptoras de embriões bovinos
Keywords: Amazonian biome; Bovine; Embryo transfer; In vitro production